Composition, cultivation and potential applications of Chlorella zofingiensis - A comprehensive review - António A. Martins (2021)
Chlorella zofingiensis has been in the center of attention due to its viability of cultivation, capability to yield various products, and applicability in various industrial sectors. Several research studies have evaluated this microalga as a bio-factory for carotenoids and lipids production, which are interesting compounds for industrial applications. The microalgae's robustness to various environmental and stress conditions such as light, temperature, salinity, and nutrients' deficiency/excess promotes its importance as a promising source of the mentioned valuable products. Hence, this study intends to review the most prominent contents of C. zofingiensis (i.e., lutein, astaxanthin, exopolysaccharides or EPS, lipids, etc.) and analyze the cultivation and stress conditions which directly influence the quality and quantity of the desired compounds. Upon review, discussions will be conducted to investigate the ability to combine stress factors to increase the contents of interest. Following an investigation over the composition and content induction approaches, several commercial applications of this microalga will be listed and explained, in particular, to obtain valuable products which have been discussed. These applications are chosen to cover multiple sectors, from medical and pharmaceutical, to food and feedstock, biofuel and energy, and wastewater treatment. The broad capability and robustness of C. zofingiensis make it a suitable investment to target more than one sector. Finally, it is discussed and presented a tentative design of a pipeline combining several applications to increase the economic viability of obtaining multiple products. (c) 2021 Elsevier B.V.